Russell-Silver Syndrome: Molecular Diagnosis of Maternal Uniparental Disomy of Chromosome 7 Using Methylation-Specific Polymerase chain Reaction Assay and Single Nucleotide polymorphisms Genotyping - 周言穎(Yen-Yin Chou); 陳建彰(Chien-Chang Chen); 郭保麟(Pao-Lin Kuo); 蔡文暉(Wen-Hui Tsai); 林秀娟(Shio-Jean Lin) (Journal of the Formosan Medical Association, 2004)
Russell-Silver syndrome (RSS) should be suspected in patients with prenatal and postnatal growth retardation. Because there is no clinical feature specific for RSS, molecular analysis is necessary to confirm the diagnosis. Recently, maternal uniparental disomy of chromosome 7 (mUPD7) has been reported in approximately 10% of RSS patients. We describe a 10-year-old Taiwanese RSS girl with prenatal and postnatal growth retardation, relative macrocephaly, a triangular face, frontal bossing, and mild fifth finger clinodactyly. Molecular diagnosis of mUPD7 was confirmed by use of methylation-specific polymerase chain reaction and haplotype analysis with single nucleotide polymorphisms (SNPs) genotyping. Analyzing the methylation status of the PEG1/MEST gene is a cost-effective screening method for mUPD7 molecular diagnosis. However, positive cases should be subsequently confirmed by haplotype analysis using SNPs genotyping or short tandem repeat markers.